Simultaneous Determination and Pharmacokinetic Comparisons of Multi-Ingredients after Oral Administration of Radix Salviae Miltiorrhizae Extract, Hawthorn Extract, and a Combination of Both Extracts to Rats - Yu-Qiang Liu; Qian Cai; Chang Liu; Feng-Wei Bao; Zhen-Qiu Zhang (Journal of Analytical Methods in Chemistry)
A simple and sensitive HPLC method was developed for simultaneous determination of danshensu (DSS), rosmarinic acid (RA), lithospermic acid (LA), salvianolic acid B (SAB), and hyperoside (HP) in rat plasma. This method validated was successfully applied to the pharmacokinetic study of the main active ingredients after oral administration of Radix Salviae Miltiorrhizae extract (SME), hawthorn extract (HTE), and a combination of both extracts (2.5 : 1) to rats. The results indicated that there have been great differences in pharmacokinetics between a single extract and a combination of both extracts. A combination of both extracts can enhance their bioavailabilities and delay the elimination of SAB and DSS in rats.